Polycarbonate composite material as well as preparation method and application thereof

Graphite nanosheets were prepared by dry ball milling and mixed with thermoplastic elastomer and boron nitride, which solved the balance between thermal conductivity and electrical insulation properties of polycarbonate-based composite materials, achieved efficient thermal conductivity and mechanical properties improvement, and was suitable for electronics The heat dissipation material of the equipment.

CN119286216APending Publication Date: 2025-01-10CHINA PETROLEUM & CHEMICAL CORP
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202310836895.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing polycarbonate-based composite materials are difficult to maintain electrical insulation while improving thermal conductivity, and the preparation process is complex and unfavorable to industrial production, which affects its application in electronic equipment.

Method used

Graphite nanosheets were prepared by dry ball milling high-purity graphite, and mixed with thermoplastic elastomer and boron nitride to prepare insulated thermally conductive polycarbonate composite materials. The dry process was used to avoid the use of solvents, simplify the process, and improve the thermal conductivity of the material. and mechanical properties.

Benefits of technology

It achieves a balance between high thermal conductivity and electrical insulation, simplifies the process flow, reduces costs, and is suitable for efficient heat dissipation materials for electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286216A_ABST
    Figure CN119286216A_ABST
Patent Text Reader

Abstract

The invention discloses a polycarbonate composite material as well as a preparation method and application thereof, and belongs to the technical field of polymer composite materials. The polycarbonate composite material is prepared from the following raw materials: graphite, a thermoplastic elastomer, polycarbonate resin and boron nitride. Carrying out dry ball milling on the graphite and the thermoplastic elastomer to obtain a mixture containing the graphite nanosheet and the thermoplastic elastomer; according to the invention, the insulating heat-conducting filler boron nitride and the conductive heat-conducting filler graphite nanosheet are mixed with the polycarbonate matrix, so that the boron nitride can isolate a conductive path of the graphite nanosheet, and the insulating heat-conducting filler boron nitride forms a heat-conducting network and maintains the electrical insulation property; and the advantage that the conductive and heat-conducting filler graphite nanosheet contributes to efficient heat conduction of the polycarbonate composite material can be fully exerted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer composite materials, and in particular to an insulating and thermally conductive polycarbonate composite material and a preparation method and application thereof. Background Art

[0002] Polycarbonate (PC) is an aromatic polymer containing a carbonate group in the main chain of the molecule. It has the characteristics of excellent impact toughness, excellent mechanical strength, excellent dimensional stability, electrical insulation, creep resistance, low moisture absorption, weather resistance, and a wide operating temperature range. It is a thermoplastic engineering plastic with excellent comprehensive performance. At the same time, it has low molding shrinkage, good dimensional stability and flame retardancy, making it an ideal material for manufacturing electronic and electrical components.

[0003] With the development of these electronic devices and components towards higher speed, higher energy, higher integration and miniaturization, local heat release has become more serious. The local heat flux density of some devices can even reach 100W / cm 2 The heat accumulated inside the equipment will not only reduce the working efficiency and stability of the device, but also greatly shorten its service life. For example, in LED lighting devices, 70% of the energy is dissipated in the form of waste heat. If this waste heat cannot be dissipated in time, the working temperature of the LED will be greatly increased. Statistics show that for every 10°C increase in working temperature, the luminous efficiency of the LED will decrease by 5%, seriously affecting its working efficiency, and its service life will also be halved; therefore, the use of high thermal conductivity materials and unique structural design to build efficient heat dissipation pathways inside electronic equipment is of great significance for its high performance and multifunctional development; however, due to the low thermal conductivity of polycarbonate itself, it has become a barrier to restrict the internal heat dissipation of electronic devices as a shell or packaging material. Therefore, in order to meet the current needs of efficient heat dissipation of electronic products and at the same time give full play to the material properties of polycarbonate itself, it is urgent to develop polycarbonate-based composite materials with high thermal conductivity, electrical insulation, high strength and high toughness.

[0004] Chinese patent CN105694413A discloses a high thermal conductivity graphene-based polycarbonate composite material, which includes the following components by weight: 50-100 parts of polycarbonate masterbatch, 1-5 parts of carbon material, 2-5 parts of maleic anhydride grafted polypropylene, 1-5 parts of plasticizer, and 0.1-1 part of coupling agent; the graphene-modified polycarbonate composite material uses zero-dimensional, one-dimensional, and two-dimensional materials to construct a three-dimensional thermal conductive network. Although it can improve the thermal conductivity of polycarbonate, the insulation performance of the composite material is not considered, and the filler is treated with a surface treatment agent for secondary treatment, which is easy to cause environmental pollution, and the addition of a surfactant will cause the thermal conductivity of the material to decrease, making it difficult to achieve large-scale application.

[0005] Chinese patent CN108070232A discloses a polycarbonate-based high thermal conductivity insulating composite material and a preparation method thereof, comprising the following raw materials in parts by weight: 30-60 parts of polycarbonate, 5-10 parts of butanediol, 10-25 parts of polyethylene, 2-5 parts of stearic acid, 2-5 parts of nano-chromium oxide, 3-6 parts of nano-carbon fibers, 2-5 parts of nano-aluminum nitride, 1-3 parts of coupling agents, and 1-5 parts of cross-linking agents; the invention utilizes the cross-linking of polymers and the organic-inorganic hybridization principle to prepare a polycarbonate composite material with high thermal conductivity and good mechanical properties. The preparation process is complicated and is not conducive to large-scale industrial production, and the thermal conductivity and mechanical properties of the composite material are not disclosed in the patent.

[0006] Chinese patent CN106700423A discloses a polycarbonate insulating thermally conductive composite material and a preparation method thereof, which is composed of an insulating thermally conductive composite material, a reinforcing matrix material and functional additives. The insulating thermally conductive composite material is an epoxy resin and polycarbonate composite, the reinforcing matrix material is glass fiber, carbon fiber core boron nitride, and the functional additives include silane coupling agents, anti-aging agents, plasticizers, flame retardants, composite stabilizers and solvents. The invention uses ultrasonic dispersion of silane coupling agents to perform secondary treatment on the filler, which is easy to cause environmental pollution, and the addition of surfactants will cause the thermal conductivity of the material to decrease. The use of organic solvents has environmental problems and cumbersome processes such as subsequent removal of solvents, which is not conducive to large-scale industrial production.

[0007] Chinese patent CN109912956B discloses an enhanced thermal conductive PC material and raw materials for preparation, as well as a preparation method and application thereof. The raw materials for preparing the enhanced thermal conductive PC material are composed of PC resin, inorganic thermal conductive filler, ionic solvent, glass fiber, toughening agent, coupling agent and optional lubricant and antioxidant. The weight ratio of the PC resin, inorganic thermal conductive filler, ionic solvent, glass fiber, toughening agent and coupling agent is (100-500): (60-500): (5-50): (30-200): (5-70): 1; the inorganic thermal conductive filler used in the invention is treated with an ionic solvent and reinforced with glass fiber. The preparation process is complicated and involves the use of solvents, which is not conducive to industrial application.

[0008] In order to obtain excellent thermal conductivity, a large amount of thermal conductive filler needs to be filled in the polycarbonate matrix. However, the thermal conductive filler will cause the mechanical properties and impact resistance of the material to decrease, and the melt viscosity of the material will also increase, affecting the processing performance. In addition, compared with electrically insulating thermal conductive fillers such as boron nitride, silicon carbide, and alumina, although electrically conductive thermal conductive fillers (graphite, graphene, carbon nanotubes, etc.) have higher thermal conductivity and contribute more to the thermal conductivity of composite materials, their own excellent electrical conductivity will also reduce the resistivity of the composite material, causing the composite material to lose its electrical insulation properties and be limited in its application in some scenarios. Summary of the invention

[0009] In view of the above situation, the present invention provides an insulating thermally conductive polycarbonate composite material, a preparation method and application thereof. The dispersion of graphite nanosheets obtained by mixing high-purity graphite and a thermoplastic elastomer and dry grinding can balance and optimize the mechanical and processing properties of the composite material. Specifically, dry ball milling of high-purity graphite is used to in-situ prepare thermally conductive filler graphite nanosheets, and then prepare the insulating thermally conductive polycarbonate composite material. No solvent is used in the process, and the process is simple, efficient, low cost, energy-saving and environmentally friendly.

[0010] In order to solve the above technical problems, the first aspect of the present invention provides a polycarbonate composite material, the raw materials of which include graphite, thermoplastic elastomer, polycarbonate resin and boron nitride;

[0011] The graphite and thermoplastic elastomer are a mixture of graphite nanosheets and thermoplastic elastomer obtained by dry ball milling. The mixture of graphite nanosheets and thermoplastic elastomer is obtained by dry ball milling of graphite and thermoplastic elastomer, and the dry ball milling loss can be ignored, that is, the weight proportions of graphite nanosheets and thermoplastic elastomer in the mixture of graphite nanosheets and thermoplastic elastomer are the same as the weight proportions of graphite and thermoplastic elastomer before dry ball milling.

[0012] According to some embodiments of the present invention, the raw materials of the polycarbonate composite material include the following components in parts by weight:

[0013] Graphite 5 to 25 parts, preferably 10 to 20 parts; for example 10 parts, 16 parts, 20 parts;

[0014] 8 to 15 parts of thermoplastic elastomer, preferably 9 to 15 parts; for example 9 parts, 10 parts, 13 parts, 15 parts;

[0015] 50 to 80 parts of polycarbonate resin, preferably 57 to 70 parts; for example 57 parts, 60 parts, 70 parts;

[0016] Boron nitride 1 to 30 parts, preferably 1 to 20 parts; for example 1 part, 5 parts, 10 parts, 15 parts, 20 parts.

[0017] According to some embodiments of the present invention, the graphite is high-purity graphite with a carbon content of >99.99%; preferably, the particle size of the high-purity graphite is 5μm to 25μm, for example, 5μm, 10μm, 15μm, 20μm, 25μm.

[0018] According to some embodiments of the present invention, the thermoplastic elastomer is in powder form with a particle size of 200 μm to 500 μm, for example, 200 μm, 300 μm, 400 μm, or 500 μm; preferably, the thermoplastic elastomer is selected from at least one of hydrogenated styrene-butadiene block copolymer (SEBS), styrene-butadiene block copolymer (SBS), and maleic anhydride grafted styrene-butadiene block copolymer.

[0019] According to some embodiments of the present invention, the polycarbonate resin has a melt mass flow rate of 12 g / 10 min to 21 g / 10 min, for example, 12 g / 10 min, 15 g / 10 min, 17 g / 10 min, and 21 g / 10 min, when the temperature is 260° C. and the load is 5 kg.

[0020] and / or, the graphite nanosheets have an average lateral size of 2 μm to 10 μm, such as 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, and an average thickness of 50 nm to 100 nm, such as 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm;

[0021] And / or, the particle size of the boron nitride is 10 μm to 35 μm, preferably 25 μm.

[0022] According to some embodiments of the present invention, the in-plane thermal conductivity of the polycarbonate composite material is ≧2 W / mK, preferably 2.0 W / mK to 2.17 W / mK;

[0023] and / or, vertical thermal conductivity ≧0.59 W / mK, preferably 0.59 W / mK to 0.64 W / mK;

[0024] and / or, a volume resistivity of 10 8 Ohmm~10 9 Ohmm.

[0025] In the dry ball milling of the present invention, under the protection of the thermoplastic elastomer, the graphite nanosheet two-dimensional thermal conductive filler obtained by exfoliation has few structural defects and large sheets, and can maintain its intrinsic thermal conductivity to a large extent; when preparing the polycarbonate composite material, boron nitride filler is added so that the boron nitride can isolate the conductive path of the graphite nanosheet, thereby further realizing the thermal conductivity and insulation performance of the polycarbonate composite material.

[0026] A second aspect of the present invention provides a method for preparing a polycarbonate composite material, comprising mixing graphite and a thermoplastic elastomer, a polycarbonate resin and boron nitride, and extruding to obtain the polycarbonate composite material.

[0027] According to some embodiments of the present invention, during the mixing, graphite and thermoplastic elastomer are first dry-milled to obtain a mixture of graphite nanosheets and thermoplastic elastomer, and then the mixture of graphite nanosheets and thermoplastic elastomer, polycarbonate resin and boron nitride are mixed; preferably, the dry milling is carried out in a ball mill, and further preferably, the rotation speed of the ball mill is 500 rpm, and the ball milling time is 3h to 12h, for example, 3h, 6h, 9h, 12h; the mixing conditions include: temperature of 20°C to 50°C, preferably 30°C, time of 5min to 10min, preferably 6min.

[0028] According to some embodiments of the present invention, the extrusion conditions include: an extrusion temperature of 250°C to 280°C, for example, 250°C, 260°C, 270°C, 280°C, and a screw speed of 150rpm to 300rpm, for example, 150rpm, 200rpm, 260rpm, 300rpm.

[0029] A third aspect of the present invention provides a polycarbonate composite material prepared by the above preparation method or an application of the above polycarbonate composite material in the preparation of electronic devices, preferably as a shell material for LED lighting devices to meet the current product demand for efficient heat dissipation.

[0030] Beneficial effects:

[0031] When preparing graphite nanosheets, the shear force generated in the dry ball milling process can cause the graphite to be peeled off into thinner graphite nanosheets, while the impact force can break the graphite into smaller-sized graphite nanosheets, and even destroy the crystal structure of the graphite into amorphous carbon. The thermoplastic elastomer is used as a solid diluent, and the molecular structure of the thermoplastic elastomer can form a strong π-π interaction with the graphite surface, thereby protecting the graphene nanosheets from the impact force generated by the ball milling, reducing the formation of amorphous carbon to the maximum extent, and preventing the graphene nanosheets obtained by peeling from reaggregating, thereby realizing in-situ dispersion of the graphite nanosheets, and obtaining graphene nanosheets with complete structures and large sheets.

[0032] The present invention adopts dry ball milling of high-purity graphite to prepare graphite nanosheet filler, which is green, environmentally friendly and efficient. The addition of thermoplastic elastomer is conducive to in-situ exfoliation and dispersion of the graphite nanosheet by ball milling, thereby enhancing the interface effect between the graphite nanosheet and the polycarbonate matrix, promoting the uniform dispersion of the graphite nanosheet in the polycarbonate matrix, and facilitating the improvement of the thermal conductivity and mechanical properties of the thermally conductive polycarbonate composite material.

[0033] The present invention uses insulating thermal conductive filler boron nitride and conductive thermal conductive filler graphite nanosheets to mix with a polycarbonate matrix, so that the boron nitride can isolate the conductive path of the graphite nanosheets, and the insulating thermal conductive filler boron nitride forms a thermal conductive network while maintaining electrical insulation performance, which can give full play to the advantages of the conductive thermal conductive filler graphite nanosheets in contributing to the efficient thermal conductivity of the polycarbonate composite material;

[0034] The high thermal conductivity insulating polycarbonate material prepared by the present invention can be applied to the shell material of LED lighting devices or the heat dissipation components in mobile phones, meeting the demand for efficient heat dissipation of current electronic and electrical products. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is a SEM photo of the graphite nanosheet prepared in Example 1;

[0036] Figure 2 is a SEM photograph of the graphite nanosheet prepared in Comparative Example 2;

[0037] Figure 3 is a SEM photograph of the graphite nanosheet prepared in Comparative Example 3;

[0038] Figure 4 This is a SEM photograph of the graphite nanosheets prepared in Comparative Example 4. DETAILED DESCRIPTION

[0039] The present invention will be further described below in conjunction with the embodiments, but the present invention is not limited by these embodiments.

[0040] The average lateral size and average thickness of the graphite nanosheets described in the present invention are measured by dispersing a trace amount of graphite nanosheets in dehydrated ethanol and diluting them multiple times; then using a micropipette to drop them on the peeled mica sheet, and after drying, obtaining a sample to be tested; using an atomic force microscope to count the lateral size and thickness of 100 graphite nanosheets, and finally calculating the average lateral size and thickness of the graphite nanosheets;

[0041] The stainless steel ball mill described in the present invention is a 11.8L vertical planetary ball mill purchased from Nanjing Angkeling Electrical Equipment Co., Ltd.

[0042] The model of the high-speed mixer described in the present invention is SHR-25A, purchased from Zhangjiagang Yili Machinery Co., Ltd.;

[0043] The twin-screw extruder described in the present invention is of model CX26, purchased from Nanjing Ruiya Extrusion Machinery Manufacturing Co., Ltd.;

[0044] The melt mass flow rate test in the present invention is carried out according to method A in standard ISO 1133-1:2011, with a temperature of 260° C. and a load of 5 kg;

[0045] The test of thermal conductivity described in the present invention adopts the plane heat source method, the equipment is hot-disk 2500-OT, and the manufacturer is Swedish Hot Disk Co., Ltd.; the calculation method is: first, the pressure molding machine is pressed for 10 minutes at a temperature of 260°C and a pressure of 10MPa, and then placed under a pressure of 10MPa for cold pressing to form two cylinders with a diameter of 30mm and a thickness of 1mm; the two cylindrical pieces are clamped on the upper and lower surfaces of the probe and compacted so that the sample surface is in full contact with the probe surface; then the hot-disk host will heat the probe through the resistance coil at the front end of the probe according to the set power, and the heat generated will inevitably diffuse into the inside of the sample, that is, the thermal conductivity of the sample is calculated by fitting based on the cooling rate of the probe as the main reference;

[0046] The volume resistivity test in the present invention is to take a rectangular parallelepiped sample with a length (L), a width (a), and a thickness (b) of 50 mm, 10 mm, and 1 mm, respectively, apply conductive silver paste on both ends of the cut sample, and then test the resistance value of the composite material by a two-point method (Keithley6487), wherein each group contains at least 5 samples, and the average value of the five samples is taken; the above-measured resistance value (R) is substituted into formula (I) to calculate the volume resistivity (ρ) of the composite material, ρ=R×ab / L(I);

[0047] The Izod notched impact strength test in the present invention is carried out in accordance with the standard GB / 1843-2008, using an XJU-22 impact tester, with a sample size of 80×10×4 mm. 3 , the notch depth is 2.0mm;

[0048] The fracture stress and strain test of the present invention is in accordance with the standard ASTM D638, using a CMT-4104 universal material testing machine, using a standard cutter to cut a dumbbell-shaped specimen with a size of 155mm×25mm×4mm at the center of the sample, wherein the length of the narrow neck portion of the sample is 85mm and the width is 10mm; under the condition of a tensile rate of 50mm / min, the sample is tested on a testing machine (SANS CMT-4104) to obtain the fracture and strain of the composite material;

[0049] The SEM images of the graphite nanosheets described in the present invention were taken using a JEOL JSM-5900LV scanning electron microscope;

[0050] The high-purity graphite in the present invention is purchased from Qingdao Xingyuan Graphite Emulsion Co., Ltd., and the carbon content is >99.99%;

[0051] The thermoplastic elastomer in the present invention is hydrogenated styrene-butadiene block copolymer (SEBS), which is purchased from China Petrochemical Group Baling Petrochemical Co., Ltd.;

[0052] The polycarbonate resin in the present invention is purchased from SABIC;

[0053] The boron nitride in the present invention was purchased from Dandong Rijin Technology Co., Ltd.

[0054] There is no special requirement for N,N-dimethylformamide and polyethylene in the present invention, and any commercially available ones can be used;

[0055] Unless otherwise specified, the parts described in the present invention are parts by weight.

[0056] Example 1

[0057] This embodiment provides a method for preparing a polycarbonate composite material, the steps are as follows:

[0058] a) Preparation of a mixture of graphite nanosheets and thermoplastic elastomer: 20 parts of high-purity graphite (particle size 5 μm), 9 parts of thermoplastic elastomer (SEBS, particle size 200 μm) and stainless steel balls were placed in an 11.8L stainless steel ball mill, the speed was set to 500 rpm, the material was taken out after ball milling for 6 hours, and the ball milling beads were removed by sieving to obtain a mixture of graphite nanosheets and thermoplastic elastomer. The average lateral size of the graphite nanosheets was 3 μm and the average thickness was 70 nm. The SEM photograph of the graphite nanosheets is shown in Figure 1 ;

[0059] b) Preparation of polycarbonate composite material: The mixture of graphite nanosheets and thermoplastic elastomer prepared above, 70 parts of polycarbonate resin (melt mass flow rate of 12 g / 10 min) and 1 part of boron nitride (particle size of 25 μm) were blended in a high-speed mixer at a temperature of 30° C. for 6 min to obtain a blend, and then the blend was added to a twin-screw extruder, the temperature was controlled at 260° C., the screw speed was 260 rpm, and the polycarbonate composite material was obtained after screw extrusion, cooling, granulation and drying; the properties of the prepared polycarbonate composite material are shown in Table 1.

[0060] Example 2

[0061] This embodiment provides a method for preparing a polycarbonate composite material, the steps are as follows:

[0062] a) Preparation of a mixture of graphite nanosheets and thermoplastic elastomer: 20 parts of high-purity graphite (particle size 15 μm), 15 parts of thermoplastic elastomer (SEBS, particle size 300 μm) and stainless steel balls were placed in an 11.8 L stainless steel ball mill, and the speed was set to 500 rpm. After 9 hours, the material was taken out and the ball milling beads were removed by sieving to obtain a mixture of graphite nanosheets and thermoplastic elastomer. The average lateral size of the graphite nanosheets was 5 μm and the average thickness was 80 nm.

[0063] b) Preparation of polycarbonate composite material: The mixture of graphite nanosheets and thermoplastic elastomer prepared above, 60 parts of polycarbonate resin (melt mass flow rate of 17 g / 10 min) and 5 parts of boron nitride (particle size of 25 μm) were blended in a high-speed mixer at a temperature of 30° C. for 6 min to obtain a blend, and then the blend was added to a twin-screw extruder, the temperature was controlled at 250° C., the screw speed was 300 rpm, and the polycarbonate composite material was obtained after screw extrusion, cooling, granulation and drying. The properties of the prepared polycarbonate composite material are shown in Table 1.

[0064] Example 3

[0065] This embodiment provides a method for preparing a polycarbonate composite material, the steps are as follows:

[0066] a) Preparation of a mixture of graphite nanosheets and thermoplastic elastomer: 20 parts of high-purity graphite (particle size 15 μm), 10 parts of thermoplastic elastomer (SEBS, particle size 300 μm) and stainless steel balls were placed in an 11.8 L stainless steel ball mill, and the speed was set to 500 rpm. After 12 hours, the material was taken out and the ball milling beads were removed by sieving to obtain a mixture of graphite nanosheets and thermoplastic elastomer. The average lateral size of the graphite nanosheets was 10 μm and the average thickness was 70 nm.

[0067] b) Preparation of polycarbonate composite material: The mixture of graphite nanosheets and thermoplastic elastomer prepared above, 60 parts of polycarbonate resin (melt mass flow rate of 21 g / 10 min) and 10 parts of boron nitride (particle size of 25 μm) were blended in a high-speed mixer at a temperature of 30° C. for 6 min to obtain a blend, and then the blend was added to a twin-screw extruder, the temperature was controlled at 270° C., the screw speed was 300 rpm, and the polycarbonate composite material was obtained after screw extrusion, cooling, granulation and drying. The properties of the prepared polycarbonate composite material are shown in Table 1.

[0068] Example 4

[0069] This embodiment provides a method for preparing a polycarbonate composite material, the steps are as follows:

[0070] a) Preparation of a mixture of graphite nanosheets and thermoplastic elastomer: 16 parts of high-purity graphite (particle size 10 μm), 9 parts of thermoplastic elastomer (SEBS, particle size 500 μm) and stainless steel balls were placed in an 11.8 L stainless steel ball mill, and the speed was set to 500 rpm. After 12 hours, the material was taken out and the ball milling beads were removed by sieving to obtain a mixture of graphite nanosheets and thermoplastic elastomer. The average lateral size of the graphite nanosheets was 3 μm and the average thickness was 50 nm.

[0071] b) Preparation of polycarbonate composite material: The mixture of graphite nanosheets and thermoplastic elastomer prepared above, 60 parts of polycarbonate resin (melt mass flow rate of 12 g / 10 min) and 15 parts of boron nitride (particle size of 25 μm) were blended in a high-speed mixer at a temperature of 30° C. for 6 min to obtain a blend, and then the blend was added to a twin-screw extruder, the temperature was controlled at 260° C., the screw speed was 200 rpm, and the polycarbonate composite material was obtained after screw extrusion, cooling, granulation and drying. The properties of the prepared polycarbonate composite material are shown in Table 1.

[0072] Example 5

[0073] This embodiment provides a method for preparing a polycarbonate composite material, the steps are as follows:

[0074] a) Preparation of a mixture of graphite nanosheets and thermoplastic elastomer: 10 parts of high-purity graphite (particle size 10 μm), 13 parts of thermoplastic elastomer (SEBS, particle size 500 μm) and stainless steel balls were placed in an 11.8 L stainless steel ball mill, and the speed was set to 500 rpm. After 3 hours, the material was taken out and the ball milling beads were removed by sieving to obtain a mixture of graphite nanosheets and thermoplastic elastomer. The average lateral size of the graphite nanosheets was 2 μm and the average thickness was 100 nm.

[0075] b) Preparation of polycarbonate composite material: The mixture of graphite nanosheets and thermoplastic elastomer prepared above, 57 parts of polycarbonate resin (melt mass flow rate of 17 g / 10 min) and 20 parts of boron nitride (particle size of 25 μm) were blended in a high-speed mixer at a temperature of 30° C. for 6 min to obtain a blend, and then the blend was added to a twin-screw extruder, the temperature was controlled at 250° C., the screw speed was 300 rpm, and the polycarbonate composite material was obtained after screw extrusion, cooling, granulation and drying. The properties of the prepared polycarbonate composite material are shown in Table 1.

[0076] Example 6

[0077] This embodiment provides a method for preparing a polycarbonate composite material, the steps are as follows:

[0078] a) Preparation of a mixture of graphite nanosheets and thermoplastic elastomer: 10 parts of high-purity graphite (particle size 10 μm), 10 parts of thermoplastic elastomer (SEBS, particle size 300 μm) and stainless steel balls were placed in an 11.8 L stainless steel ball mill, and the speed was set to 500 rpm. After 6 hours, the material was taken out and the ball milling beads were removed by sieving to obtain a mixture of graphite nanosheets and thermoplastic elastomer. The average lateral size of the graphite nanosheets was 3 μm and the average thickness was 70 nm.

[0079] b) Preparation of polycarbonate composite material: The mixture of graphite nanosheets and thermoplastic elastomer prepared above, 60 parts of polycarbonate resin (melt mass flow rate of 21 g / 10 min) and 20 parts of boron nitride (particle size of 25 μm) were blended in a high-speed mixer at a temperature of 30° C. for 6 min to obtain a blend, and then the blend was added to a twin-screw extruder, the temperature was controlled at 280° C., the screw speed was 260 rpm, and the polycarbonate composite material was obtained after screw extrusion, cooling, granulation and drying. The properties of the prepared polycarbonate composite material are shown in Table 1.

[0080] Comparative Example 1

[0081] This comparative example provides a method for preparing a polycarbonate composite material, and the steps are as follows:

[0082] a) Preparation of a mixture of graphite nanosheets and thermoplastic elastomer: 10 parts of high-purity graphite (particle size 10 μm), 10 parts of thermoplastic elastomer (SEBS, particle size 300 μm) and stainless steel balls were placed in an 11.8 L stainless steel ball mill, and the speed was set to 500 rpm. After 6 hours, the material was taken out and the ball milling beads were removed by sieving to obtain a mixture of graphite nanosheets and thermoplastic elastomer. The average lateral size of the graphite nanosheets was 3 μm and the average thickness was 70 nm.

[0083] b) Preparation of polycarbonate composite material: The mixture of graphite nanosheets and thermoplastic elastomer prepared above and 60 parts of polycarbonate resin (melt mass flow rate is 21g / 10min) are blended in a high mixer at a temperature of 30°C for 6 minutes to obtain a blend, and then the blend is added to a twin-screw extruder, the temperature is controlled at 280°C, the screw speed is 260rpm, and the polycarbonate composite material is obtained after screw extrusion, cooling, granulation and drying. The properties of the prepared polycarbonate composite material are shown in Table 1.

[0084] Comparative Example 2

[0085] This comparative example provides a method for preparing a polycarbonate composite material, and the steps are as follows:

[0086] a) Preparation of graphite nanosheets: 10 parts of high-purity graphite (particle size 10 μm) and stainless steel balls were placed in an 11.8L stainless steel ball mill, and the speed was set to 500 rpm. After 6 hours, the material was taken out and the ball milling beads were removed by sieving to obtain graphite nanosheets. In the ball milling process of the graphite nanosheet preparation, a large number of spherical agglomerates (amorphous carbon) appeared due to the absence of a solid medium, and the average lateral size and average thickness of the obtained graphite nanosheets could not be determined; the SEM photo of the graphite nanosheet is shown in Figure 2 ;

[0087] b) Preparation of polycarbonate composite material: The graphite nanosheets prepared above, 60 parts of polycarbonate resin (melt mass flow rate of 21 g / 10 min) and 20 parts of boron nitride (particle size of 25 μm) were blended in a high-speed mixer at a temperature of 30° C. for 6 min to obtain a blend, and then the blend was added to a twin-screw extruder, the temperature was controlled at 280° C., the screw speed was 260 rpm, and the polycarbonate composite material was obtained after screw extrusion, cooling, granulation and drying. The properties of the prepared polycarbonate composite material are shown in Table 1.

[0088] Comparative Example 3

[0089] This comparative example provides a method for preparing a polycarbonate composite material, and the steps are as follows:

[0090] a) Preparation of graphite nanosheets: 10 parts of high-purity graphite (particle size 10 μm), 70 parts of N,N-dimethylformamide (DMF) and stainless steel balls were placed in an 11.8L stainless steel ball mill, and the speed was set to 500 rpm. After 6 hours, the material was taken out, the ball mill beads were removed, and the solvent was removed to obtain graphite nanosheets. The average lateral size of the graphite nanosheets was 1 μm and the average thickness was 300 nm. The SEM photo of the graphite nanosheets is shown in Figure 3 ;

[0091] b) Preparation of polycarbonate composite material: The graphite nanosheets prepared above, 60 parts of polycarbonate resin (melt mass flow rate of 21 g / 10 min) and 20 parts of boron nitride (particle size of 25 μm) were blended in a high-speed mixer at a temperature of 30° C. for 6 min to obtain a blend, and then the blend was added to a twin-screw extruder, the temperature was controlled at 280° C., the screw speed was 260 rpm, and the polycarbonate composite material was obtained after screw extrusion, cooling, granulation and drying. The properties of the prepared polycarbonate composite material are shown in Table 1.

[0092] Comparative Example 4

[0093] This comparative example provides a method for preparing a polycarbonate composite material, and the steps are as follows:

[0094] a) Preparation of a mixture of graphite nanosheets and ultra-high molecular weight polyethylene: 10 parts of high-purity graphite (particle size 10 μm), 10 parts of ultra-high molecular weight polyethylene (molecular weight 2 million) and stainless steel balls were placed in an 11.8L stainless steel ball mill, and the speed was set to 500 rpm. After 6 hours, the material was taken out and the ball milling beads were removed by sieving to obtain a mixture of graphite nanosheets and ultra-high molecular weight polyethylene. The average lateral size of the graphite nanosheets was 2 μm and the average thickness was 200 nm. The SEM photo of the graphite nanosheets is shown in Figure 4 ;

[0095] b) Preparation of polycarbonate composite material: The mixture of graphite nanosheets and ultra-high molecular weight polyethylene prepared above, 60 parts of polycarbonate resin (melt mass flow rate of 21 g / 10 min) and 20 parts of boron nitride (particle size of 25 μm) were blended in a high-speed mixer at a temperature of 30° C. for 6 min to obtain a blend, and then the blend was added to a twin-screw extruder, the temperature was controlled at 280° C., the screw speed was 260 rpm, and the polycarbonate composite material was obtained after screw extrusion, cooling, granulation and drying. The properties of the prepared polycarbonate composite material are shown in Table 1.

[0096] Comparative Example 5

[0097] This comparative example provides a method for preparing a polycarbonate composite material, and the steps are as follows:

[0098] 57 parts of polycarbonate resin (melt mass flow rate of 17 g / 10 min), 20 parts of boron nitride (particle size 25 um), and 10 parts of thermoplastic elastomer (SEBS, particle size 500 μm) were blended in a high mixer at a temperature of 30° C. for 6 minutes to obtain a blend, and then the blend was added to a twin-screw extruder, the temperature was controlled at 250° C., the screw speed was 300 rpm, and the polycarbonate composite material was obtained after screw extrusion, cooling, granulation, and drying. The properties of the prepared polycarbonate composite material are shown in Table 1 below.

[0099] Comparative Example 6

[0100] This comparative example provides a method for preparing a polycarbonate composite material, and the steps are as follows:

[0101] 20 parts of high-purity graphite (particle size 10 μm), 10 parts of thermoplastic elastomer (SEBS, particle size 300 μm) and 70 parts of polycarbonate resin (melt mass flow rate of 17 g / 10 min) were blended in a high mixer at a temperature of 30° C. for 6 minutes to obtain a blend, and then the blend was added to a twin-screw extruder, the temperature was controlled at 280° C., the screw speed was 260 rpm, and the polycarbonate composite material was obtained after screw extrusion, cooling, granulation and drying. The properties of the prepared polycarbonate composite material are shown in Table 1 below.

[0102] Table 1 Performance test results of polycarbonate composite materials prepared in Examples 1-6 and Comparative Examples 1-5

[0103]

[0104] As can be seen from Table 1, the insulating thermally conductive polycarbonate composite materials obtained by the preparation methods provided in Examples 1-5 of the present invention have excellent mechanical properties and insulating thermally conductive properties, and can be applied to the heat sink and housing application fields of electronic and electrical equipment;

[0105] In Comparative Example 1, compared with Example 6, the addition of boron nitride was reduced, and the insulating thermal conductivity of the prepared insulating thermally conductive polycarbonate composite material was significantly reduced, and the mechanical properties also decreased to a certain extent; in Comparative Examples 2-4, compared with Example 6, no thermoplastic elastomer was added, DMF was used to replace the thermoplastic elastomer, and ultra-high molecular weight polyethylene was used to replace the thermoplastic elastomer, respectively, and the insulating thermal conductivity of the prepared insulating thermally conductive polycarbonate composite material was significantly reduced, and the mechanical properties also decreased to a certain extent; in Comparative Example 5, compared with Example 5, no mixture containing graphite nanosheets and thermoplastic elastomer was added, and only unground thermoplastic elastomer was added, and the prepared insulating thermally conductive polycarbonate composite material had a significantly reduced insulating thermal conductivity, and the mechanical properties also decreased to a certain extent. The insulating thermal conductivity and mechanical properties of the thermal polycarbonate composite material are significantly reduced. In Comparative Example 6, the graphite and the thermoplastic elastomer are not ground, and the insulating thermally conductive polycarbonate composite material prepared directly using graphite, thermoplastic elastomer and polycarbonate has significantly reduced thermal conductivity and electrical conductivity, and poor mechanical properties. Therefore, it is confirmed that the present invention uses insulating thermally conductive filler boron nitride and conductive thermally conductive filler graphite nanosheets to mix with the polycarbonate matrix, so that boron nitride can isolate the conductive path of the graphite nanosheet, and the insulating thermally conductive filler boron nitride forms a thermally conductive network while maintaining electrical insulation performance, which can give full play to the advantages of the conductive thermally conductive filler graphite nanosheets in contributing to the efficient thermal conductivity of the polycarbonate composite material.

[0106] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A polycarbonate composite material, characterized in that: The raw materials of the polycarbonate composite material include graphite, thermoplastic elastomer, polycarbonate resin and boron nitride; The graphite and the thermoplastic elastomer are subjected to dry ball milling to obtain a mixture of graphite nanosheets and thermoplastic elastomer.

2. The polycarbonate composite material according to claim 1, characterized in that: The raw materials of the polycarbonate composite material include the following components in parts by weight:

3. The polycarbonate composite material according to claim 1 or 2, characterized in that: The graphite is high-purity graphite with a carbon content of >99.99%; and / or the particle size of the graphite is 5 μm to 25 μm.

4. The polycarbonate composite material according to any one of claims 1 to 3, characterized in that: The thermoplastic elastomer is in powder form with a particle size of 200 μm to 500 μm; And / or, the thermoplastic elastomer is at least one selected from hydrogenated styrene-butadiene block copolymer, styrene-butadiene block copolymer, and maleic anhydride grafted styrene-butadiene block copolymer.

5. The polycarbonate composite material according to any one of claims 1 to 4, characterized in that: The polycarbonate resin has a melt mass flow rate of 12 g / 10 min to 21 g / 10 min measured at a temperature of 260° C. and a load of 5 kg; And / or, the graphite nanosheets have an average lateral size of 2 μm to 10 μm and an average thickness of 50 nm to 100 nm; And / or, the particle size of the boron nitride is 10 μm to 35 μm, preferably 25 μm.

6. The polycarbonate composite material according to any one of claims 1 to 5, characterized in that: The in-plane thermal conductivity of the polycarbonate composite material is ≧2 W / mK, preferably 2.0 W / mK to 2.17 W / mK; and / or, vertical thermal conductivity ≧0.59 W / mK, preferably 0.59 W / mK to 0.64 W / mK; and / or, a volume resistivity of 10 8 Ohmm~10 9 Ohmm.

7. A method for preparing the polycarbonate composite material according to any one of claims 1 to 6, characterized in that: The method comprises mixing graphite, thermoplastic elastomer, polycarbonate resin and boron nitride and extruding to obtain the polycarbonate composite material.

8. The preparation method according to claim 7, characterized in that: During the mixing, graphite and thermoplastic elastomer are first dry-milled to obtain a mixture of graphite nanosheets and thermoplastic elastomer, and then the mixture of graphite nanosheets and thermoplastic elastomer, polycarbonate resin and boron nitride are mixed; preferably, the dry milling is carried out in a ball mill, and further preferably, the rotation speed of the ball mill is 500 rpm, and the ball milling time is 3h to 12h; the mixing conditions include: temperature of 20°C to 50°C, and time of 5min to 10min.

9. The preparation method according to claim 7 or 8, characterized in that: The extrusion conditions include: an extrusion temperature of 250° C. to 280° C. and a screw speed of 150 rpm to 300 rpm.

10. Use of the polycarbonate composite material according to any one of claims 1 to 6 or the polycarbonate composite material prepared by the preparation method according to any one of claims 7 to 9 in preparing electronic devices.

Citation Information

Patent Citations

  • High-thermal-conductivity graphene-based polycarbonate composite material and preparation method thereof

    CN105694413A

  • Polycarbonate insulating heat-conducting composite material and preparation method thereof

    CN106700423A

  • Polycarbonate based high-thermal-conductivity insulating composite material and preparation method thereof

    CN108070232A

  • A thermally conductive PC material, its raw materials, preparation method, and applications

    CN109912956B

  • Thermally conducting and electrically insulating moldable compositions and methods of manufacture thereof

    CN101568577A